Predicting the impacts of climate change on the distribution of European syngnathids over the next century - Monteiro, Nuno; Pinheiro, Sara; Magalhães, Susana; Tarroso, Pedro; Vincent, Amanda (Frontiers in Marine Science, 2023)
At the latitudinal interval that encompasses Europe, due to the gradual seawater warming imposed by climate change, there is now continuing evidence for a widespread pattern of poleward range shifts, often translated by expansions in the northern leading edges of distribution and contraction episodes at the southern boundaries. As the distribution of biodiversity is far from static, it seems imperative that we can predict changes in species’ geographic ranges to potentially circumvent severe biodiversity losses in the near future. Here, we focus on syngnathids, flagship species and umbrella taxa for coastal marine ecosystems, and attempt to identify areas of environmental suitability in Europe over the next century, according to distinct greenhouse gas concentration trajectories. Our results seamlessly match the general and region-specific impacts of climate change projections for European seas. Especially within the Atlantic Coast, species are expected to continue poleward range shifts, with the hotspot of syngnathid diversity remaining around the Celtic-Biscay Shelf, albeit with slightly distinct species composition from that of present day. The most dramatic changes are expected within semi-enclosed areas such as the Baltic, the Mediterranean and the Black Sea, where present-day endemic species diversity is likely to plunge, especially under a ‘business-as-usual’ scenario. When looking at the potential protective role of ‘no-take’ marine protected areas (MPAs) on European syngnathids, a clear latitudinal asymmetry emerged. From the Atlantic diversity hotspot downwards, and especially in the Mediterranean and Black Sea, the current ‘no-take’ MPA layout, if it remains static, will not be especially effective in either safeguarding syngnathid diversity or delaying the expected gradual species disappearance. Europe needs to be prepared to implement, at a continental scale, coordinated conservation measures aimed at preventing (or delaying, at the very least) the loss of its marine endemic species. As umbrella species, conservation efforts aimed at syngnathids will surely have a positive impact on coastal ecosystems.